Penggunaan Metode Resiprokal untuk Meningkatkan Keterampilan Pasing Bawah Bolavoli pada Siswa SMAN 01 Batang Lupar Kabupaten Kapuas Hulu - Iskandar; Dewi, Utami; April Liani, Lorensa (Journal Sport Academy, 2023)
The goal that was achieved in this study was to find out about "efforts to improve passing skills in volleyball games through the reciprocal method in class X A students at SMA Negeri 01 Batang Lupar, Kapuas Hulu Regency. After being given learning to pass under volleyball properly and correctly, students experienced an increase. What was used in this study was descriptive research. The form used in this research is the writing of class actions, using cycles, where the stages of each cycle are: plans, actions, observations, and reflections. The research results showed an increase in each cycle after being given the reciprocal method. The data showed that the learning outcomes of passing under volleyball games carried out by students increased from 8.33% in the initial conditions to 41.66% and at the end of cycle I and experienced an increase to 77. 77% at the end of cycle II. The target achievement indicator in cycle II is 75%. From the results of student learning shown in the percentage of completeness of student learning outcomes is 77.77%, meaning that the research target was achieved in cycle II has been achieved or has met the research target.